Penyuluhan Fisioterapi Tentang Inkontinensia Urin Pada Lansia Di Posyandu Kelurahan Gadang Kota Malang - Rizki Aulia Ramadhanti; Rakhmad Rosadi; Indah Ningtiyas Hidayanti (Universitas 45 Surabaya, 2024)
Elderly are people who have reached the age of 60 years and is experiencing the aging process. In the aging process there will be a decrease in body function, so that it will cause problems in physical, psychological, mental, and social decline. Problem that are often found in the elderly is urinary incontinence. Urinary Incontinence is involuntary urination and pose a social or hygienic problem. The risk of urinary incontinence can be reduced by doing Kegel Exercise. The aim of this counseling is to provide education to the elderly in order to reduce the risk of urinary incontinence in Gadang Village, Malang. The method used is by providing leaflet as a media for counseling, giving pretest-posttest, and evaluating participants’ knowledge of the material. The result of this activity were participants showed a positive attitude during the activity and can increase the elderly’s understanding about urinary incontinence